Temporal sequence of deformation twinning in CoCrNi under tribological load. (May 2023) - Dollmann, Antje; Rau, Julia S.; Bieber, Beatrix; Mantha, Lakshmi; Kübel, Christian; Kauffmann, Alexander; Tirunilai, Aditya Srinivasan; Heilmaier, Martin; Greiner, Christian
Abstract: Microstructural evolution under tribological load is known to change the friction and wear response of the entire tribological system. It is however not yet fully understood, how these changes take place on an elementary, mechanistic level. Revealing the temporal sequence of deformation mechanisms under a tribological load by experiments is scarce. The discrete strain release in the case of deformation twinning allows the identification of their temporal sequence. Therefore, a medium stacking fault energy material, namely CoCrNi, was investigated due to the significant contribution of deformation twinning to the overall deformation at room temperature. The investigated grain showed three activated twin systems. The evolution sequence of these is discussed critically based on several twin intersection mechanisms. The experimental analysis decodes the temporal sequence of the active twinning systems of highest resolved shear stresses for the first time. This approach gives experimental indications for the stress field under tribological load. Graphical abstract: Image, graphical abstract